New Genre Arctic Art and Art Education Exhibition : Greetings from the Arctic: An Exhibition of Cross-Cultural Connections and Arctic Narratives, 2024 - Rylander, Sara; Gårdvik, Mette; Stoll, Karin; Sørmo, Wenche; Manninen, Annamari; Pennanen, Anniina; Pietilä, Virve; Ignatius, Aleksi; Lin, Ni; Jäälinoja, Aino; Lylykoski, Sade; Terävä, Kuutti (Stormen Concert Hall, 2024)
The Greetings from the North stands as a beacon of cultural connectivity and youthful expression in the Arctic realm. This exhibition seeks to weave together the younger generation in a collaborative project of artistic and environmental dialogue. At the heart of this exhibition are personalized postcards, created and exchanged by pupils residing in diverse Arctic- and near Arctic locations such as northern Finland, Norway and Sweden. These postcards are expressions of individual thoughts, concerns, and visions related to the Arctic’s unique environment and cultural heritage. Each postcard is a narrative thread, contributing to a larger tapestry that refects life and challenges in the Arctic. A visual symposium of Arctic stories, fostering intergenerational and cross-cultural dialogue. This exhibition invites viewers to embark on a journey through the North, where each postcard is a greeting, an insight, and an invitation to understand and appreciate the rich tapestry of Arctic life.